Analisis Struktur, Perilaku dan Kinerja Pasar Bawang Merah Varietas Lokal di Kabupaten Sumenep - Sindi Arista Rahman; Hopid Hopid; Purwati Ratna Wahyuni (Fakultas Pertanian, Universitas Timor, 2023)
The problem of large marketing margins, share received by small farmers and high marketing costs as a manifestation of the market performance of local varieties of shallots which are assumed to be inefficient in Sumenep Regency needs to be studied and analyzed. This study aims to analyze the structure, behavior and market performance of the local variety of shallot Rubaru. The location of the research was conducted in the District of Rubaru with the consideration that the location is the producer of shallots with the largest variety in Sumenep Regency. The research was carried out in July-October 2022. The farmer sampling method used simple random sampling of 40 farmers and marketing agencies used the Snowball Sampling method. Sources of data in this study are primary data and secondary data. The analytical tools used are descriptive methods and analysis of structure, conduct, performance (SCP). The research data explains that the market structure of local variety shallots at the farmer level tends to form a monopolistic competition market while at the trader level an imperfect market is formed, namely oligopoly or oligopsony. Most of those who act as price makers are traders due to limited market information owned by local varieties of shallot farmers. Meanwhile, market behavior at the farmer level tends to act as a price taker even though they have made a bargaining process. The market performance of local varieties of shallots in Sumenep Regency can be concluded as efficient because the large share of farmers in the first and second channels has reached 40%. Meanwhile, based on MEI (Marketing Efficiency Index) the second channel is more efficient than the first channel because the second channel is the shortest channel, meaning that it does not involve many marketing agencies.